Determination of the static and kinetic friction coefficients between the catalyst layer and the microporous layer - influence of the MEA components and its assembly conditions - Ouerghemmi, Marwa; Carral, Christophe; Blachot, Jean-François; Marty, Clémence; Dumain, Antoine; Mele, Patrice (International journal of hydrogen energy, 2024)
Membrane electrode assemblies (MEA) are composed of five principal layers: two gas diffusion layers on top of two catalyst layers surrounding the membrane. The understanding of the mechanical behavior at the different interfaces of the MEA is therefore essential and will be the subject of this study through the development of a new methodology to evaluate the friction coefficients between the different layers. The analysis of the MEA components and their assembly process impact will be considered. A morphological analysis based on confocal microscopy observations of the catalyst layer/microporous layer interface was conducted to evaluate the roughness of the different surfaces submitted to friction. Results show that the static friction increases with the addition of microporous layers and catalyst layers on their substates. The friction coefficients also increase after a low pressure hot pressing but they surprisingly decrease after an assembly performed at a high pressure. [Display omitted] •A new method is developed to measure the friction coefficient of MEA interfaces.•The influence of the MEA material and process on the friction coefficient is analyzed.•Morphological analysis of the surfaces of the MEA component were performed.•Hot-pressing step allows to tune the mechanical properties of MEA interfaces.